Investigating problem-posing during math walks in informal learning spaces - Wang, Min; Walkington, Candace (Frontiers in Psychology, 2023)
Informal mathematics learning has been far less studied than informal science learning – but youth can experience and learn about mathematics in their homes and communities. “Math walks” where students learn about how mathematics appears in the world around them, and have the opportunity to create their own math walk stops in their communities, can be a particularly powerful approach to informal mathematics learning. This study implemented an explanatory sequential mixed-method research design to investigate the effects of problem-posing activities in the math walks program on high school students’ mathematical outcomes. The math walks program was implemented during the pandemic and was modified to an online program in which students met with instructors via online meetings. The researchers analyzed students’ problem-posing work, analyzed students’ responses to a mathematics interest survey before and after the program, and compared the complexity of their self-generated problems in pre- and post-assessments and different learning activities in the program. The results suggest that students posed more complex problems in free problem-posing activities than in semi-structured problem-posing. Students also posed more complex problems in the post-survey than in the pre-survey. Additionally, students’ mathematical dispositions did not change significantly from the pre-survey to post-survey. However, the qualitative analyses revealed that students felt that they started to think more deeply, ask more questions, and connect topics and content they learned about at school to everyday objects and real-life scenarios.